2009
DOI: 10.1177/147323000903700233
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and the Effect on Social Status among Slovenian Women after Breast Cancer Treatment

Abstract: This study investigated whether the type of surgical procedure used to treat breast cancer (mastectomy versus breastconserving lumpectomy) had any effect on the quality of life and social status of women. The prospective analysis included 382 women newly diagnosed with nonmetastatic breast cancer who had undergone a surgical intervention for breast carcinoma at our institution: 198 patients had undergone mastectomy with axillary lymphadenectomy and 184 patients had undergone breast-conserving lumpectomy with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
2
9
0
3
Order By: Relevance
“…However, this study found mastectomy to be related with emotional, cognitive, social and body image function. The finding were in line with earlier results of Moro-Valdezate et al (2014), Park et al (2011), Janz et al (2005, Hartl et al (2003), Gorisek et al (2009), Chang et al (2007, Montazeri (2008). All these studies discussed strong association between mastectomy and discontentment with body image.…”
Section: Discussionsupporting
confidence: 82%
“…However, this study found mastectomy to be related with emotional, cognitive, social and body image function. The finding were in line with earlier results of Moro-Valdezate et al (2014), Park et al (2011), Janz et al (2005, Hartl et al (2003), Gorisek et al (2009), Chang et al (2007, Montazeri (2008). All these studies discussed strong association between mastectomy and discontentment with body image.…”
Section: Discussionsupporting
confidence: 82%
“…One study showed that women who underwent mastectomy reported higher scores regarding difficulty with vaginal lubrication than those who underwent conservative surgery (27) .…”
Section: Discussionmentioning
confidence: 99%
“…30 A comparative study between mastectomy and breast-conserving therapy showed that 38% of the patients submitted to mastectomy declared that they were dissatisfied with their body image, while patients who had been submitted to breast-conserving therapy did not report dissatisfaction with their body. 31 Patients submitted to breast-conserving therapy were found to be more satisfied with their appearance, with higher levels of satisfaction with their body image compared with those submitted to mastectomy with breast reconstruction. These findings are in agreement with those reported in a study conducted in Germany, in which a sample of 112 patients was evaluated, with results showing that the women submitted to breast-conserving therapy had a better image of their body compared with those submitted to mastectomy and reconstruction.…”
Section: Discussionmentioning
confidence: 93%